2012
DOI: 10.1097/brs.0b013e31822dd69b
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Intramedullary Pressure in Thoracic Kyphotic Deformity

Abstract: Thoracic kyphosis less than +51° resulted in no meaningful increase in IMP, whereas kyphosis measuring +51° to +63° resulted in minor increases in IMP. After the thoracic kyphosis exceeded +63°, IMP increased significantly. ΔIMP with spinal alignment may help explain the wide range of "normal" thoracic neutral upright sagittal alignment in studies of asymptomatic adult individuals and may help further define thoracic kyphotic deformity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…First, kyphotic deformity may induce anterior spinal cord pathology through direct compression against the posterior vertebral body and may increase longitudinal spinal cord tension due to tethering by the dentate ligaments and cervical nerve roots. 18,30,31 Sagittal imbalance may itself result in neck pain, muscle fatigue, dysphagia, and alterations in visual horizon. 5,23 Compensation for global or regional sagittal imbalance places stress on the surrounding ligaments, muscles, and soft tissues and may result in increased pain and fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…First, kyphotic deformity may induce anterior spinal cord pathology through direct compression against the posterior vertebral body and may increase longitudinal spinal cord tension due to tethering by the dentate ligaments and cervical nerve roots. 18,30,31 Sagittal imbalance may itself result in neck pain, muscle fatigue, dysphagia, and alterations in visual horizon. 5,23 Compensation for global or regional sagittal imbalance places stress on the surrounding ligaments, muscles, and soft tissues and may result in increased pain and fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…In a dynamic flexion cadaveric study, Farley et al [9] found that, in thoracic kyphosis exceeding 63°, spinal cord intramedullary pressure increased significantly compared with less substantial curves in the same specimen. However, a change of intramedullary pressure with progressive increases in the kyphosis angle on specimens did not correlate with spinal cord stenosis in the thoracic spine [9].…”
Section: Spinal Cord Ischemiamentioning
confidence: 99%
“…For this phenomenon, the pathological change in spinal TB possibly started as a result of chronic vertebral destruction and kyphotic deformity that subsequently induced the compression of the spinal cord, thereby causing neurological deficits, which differ from an acute spinal cord injury. In other words, adaptations may be observed with chronic deformity, although the alleviation of all pressure changes in the vertebral canal by chronicity cannot be assumed (4). Hence, the therapeutic effect of rapid spinal cord decompression was not necessarily better than that of a slightly delayed decompression.…”
Section: Statistical Resultsmentioning
confidence: 99%